It's not all about price: factors associated with roll-your-own tobacco use among young people - a qualitative study - Elizabeth Breslin; Joan Hanafin; Luke Clancy (BMC, 2018)
Abstract Background Smoking prevalence in Ireland is falling in all age groups, but the prevalence of roll-your-own (RYO) tobacco use is rising among young people. This qualitative study aims to explore and understand the factors associated with young people's use of RYO products. Methods Semi-structured individual and focus group interviews were conducted with young people aged 16-22 years. Participants were recruited from a higher education institution and youth organisations working with early school leavers across Dublin. In total, there were 62 participants in the study, consisting of 22 individual interviews and eight focus group interviews with 40 participants. Categoric and thematic data analysis was used to generate the findings. Results We identified two broad themes, incentivising and disincentivising factors. The lower cost of RYO products compared to pre-manufactured cigarettes was the most important incentive for users. However, other product characteristics, such as the artisanal factors associated with RYO products were also found. Social and environmental influences were apparent, in which certain groups and environments facilitated and normalised RYO practices. Amenities and facilities often provided smokers with normalised spaces which could be dedicated to the enactment of rolling practices and to the creation and maintenance of social bonds with other users. Disincentives included negative features related to the product itself, adverse health effects, and the effects of tobacco denormalisation. Conclusions While the lower cost of RYO products is very important for young smokers, other product characteristics and influences also incentivise and disincentivise use. A more comprehensive understanding of the multi-dimensional appeal of these products will assist policymakers to target strategies to reduce the attractiveness to young smokers of these products.